KOMPOSISI UNSUR DAN KARAKTERISASI MINERAL MAGNETIK DALAM RED MUD, RESIDU BAUKSIT DI PT. INDONESIA CHEMICAL ALUMINA (ICA) KALIMANTAN BARAT (ELEMENTAL COMPOSITION AND MINERAL CHARACTERISTICS OF MAGNETIC RED MUD, BAUXITE RESIDUE AT PT. INDONESIA CHEMICAL ALUMINA (ICA), WEST KALIMANTAN) - Titin Anita Zaharah; Wanda Rossalina; Imelda Hotmarisi Silalahi (Tanjungpura University, 2021)
Red mud or commonly called bauxite residue is solid waste generated from the purification of bauxite into alumina through the Bayer process. The red mud was initially dried under the sun then was magnetically separated to give magnetic sand. The magnetic sand was neutralized using copious of water, refined and then characterized using XRF and XRD methods. The results show that the main elements contained in the magnetic sand from the red mud are silicon, aluminum, iron, titanium, and magnesium. XRD analysis using Search-Match followed by the calculation using Rietveld refinement showed that the sand consisted of ferrosillite (55.3%), hematite (33.9%) and ilmenite (10.7%). Elemental analysis using XRF showed the percentage of Fe 29.15%, Si 22.49%, Ca 3.19%, and Ti 2.92%, followed by other elements with low percentages.